Self-perception and performance : exploratory research into the narcissists' first 20 months within a corporate graduate recruitment programme : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Human Development Studies at Massey University, Palmerston North, New Zealand - Simpson, Jeff (Massey University, 2012)
The intent of this exploratory study was to examine the nature and impact of narcissism in the early career stages of a graduate cohort, where there has previously been little applied narcissism research. Self-reports on self-perception and critical self-insight were obtained individually from 63 new recruits in a multi-national company as part of a graduate recruitment programme. Self-report data were collected on day one of the recruits’ induction programme followed by repeated data collections at nine months and at twenty months into their employment. In addition, at months nine and twenty, two line managers of each recruit completed indicators on their perceptions of the recruits’ actual work performance. Using a newly designed narcissistic traits indicator, line managers also indicated their views of each recruit’s narcissistic tendencies. Results obtained indicated ten of the sixty three graduates had significant narcissistic tendencies. The self-ratings of recruits were subsequently compared to their actual performance as rated by their managers. The self-perceptions of those identified as having narcissistic tendencies were also compared to self-ratings and performance of peers displaying little or no narcissistic tendencies. In both the first and second years of employment, the results indicated that those viewed as having narcissistic tendencies significantly self-enhanced more than the non-narcissists and despite their comparative higher self-rating, narcissists underperformed in their role in comparison to non-narcissists. Narcissists’ self-perception was less consistent over twenty months, indicating a less stable sense of self than the non-narcissists. A critical self-insight (CSI) self-perception gauge was developed for assessing degree and style of self-critique. Although analyses revealed five clusters of sub-scales, the narcissists’ CSI was significantly different from non-narcissists on only one of these clusters; they reported as being less emotive-sensitive than did the non-narcissists. Narcissists were overall less self-critical than non-narcissists. In light of these findings, developmental and environmental influences of narcissism are discussed, along with the effect of such traits both for the hiring organization and for the narcissistic individual within the first 20 months of career induction.
Keywords: Graduate work performance; Narcissism; Employee attitudes; Self-perception